Policy Evaluation of Post 2013 Curriculum on Madrasah Ibtidaiyah - Maulidayani Maulidayani; Syafaruddin Syafaruddin (EDUTEC : Journal of Education And Technology, 2021)
The purpose of this research is to discuss 1. Madrasah Ibtidaiyah Curriculum Planning Post Curriculum 2013 in MIN 4 Medan City. 2. Implementation of Madrasah Ibtidaiyah Curriculum Policy Post Kurikulm 2013 in MIN 4 Medan City. 3. Concept of Evaluation of Madrasah Ibtidaiyah Curriculum Policy Post Curriculum 2013 I MIN 4 Medan City, this research method is using literature and field. Literature research is used to look for references related to the Evaluation of Post-Curriculum Curriculum Policy 2013 which is applicable and in accordance with the National Education Law, while field research is used to obtain direct information in the field related to the management of the 2013 Post Curriculum Curriculum Policy Evaluation in the madrassa that is the research site. The results of this research are curriculum is very closely related to the goals to be achieved, the material to be studied, the learning process to be implemented, and the evaluation that will be done as a form to find out the success rate of learning activities that have been implemented. Likewise with MIN 4 Medan City, then in the implementation of learning activities have been adjusted to the existing design. .